Lee Kuan Yew and Singapore’s foreign policy : a productive iconoclasm - Chong, Alan (2015)
Lee Kuan Yew’s mark on Singapore’s foreign policy is that of applying counterintuitive strategies to improve the island state’s international standing. In retrospect, this has ensured Singapore’s long term viability as a sovereign nation-state.